THE INFLUENCE OF FUNDAMENTAL FACTORS ON STOCK RETURNS BEI MANUFACTURING COMPANY IN THE PERIOD 2009-2015 - Permatasari, Fransisca Indah; Kennedy, Posma Sariguna Johnson (Fundamental Management Journal, 2017)
This study aimed to analyze the influence of Economic Value Added, Return on Equity, Debt To Equity and Price Earning Ratio of stock returns. The population in this study are all manufacturing companies listed on the Stock Exchange from 2009 to 2015 period. This type of sampling in this study using purposive sampling technique. The data used in this research is secondary data in the form of data that is so or publication.The results showed that the return on equity negative effect on stock returns in the 2009-2015 period manufacturing company, Debt To Equity negative effect on stock returns in manufacturing companies 2009-2015dan period Price Earning Ratio positive effect on stock returns in the 2009-2015 period manufacturing company , While the Economic Value Added is not a positive effect on stock returns in the period from 2009 to 2015 manufacturing companies.Keywords: Manufacturing Companies, Economic Value Added, Return on Equity, Debt To Equity, Price Earning Ratio, Stock Returns.